Analisa Penurunan Vakum Kondesor Tipe Permukaan PLTGU Grati - Jasmid Edy; Erlina Erlina; Anuri Anuri (JURNAL POWERPLANT, 2015)
Loss of heat from the steam cycle power plants are mostly due to the heat removed through the condenser. condenser serves to change the output steam turbine (exhaust steam) into a condensate water through the process of heat transfer between steam and cooling water. Grati PLTGU condenser-type surface (surface condenser) with cooling in the form of sea water as much as 46.070 m3 / h decreased vacuum reaches 665 mmHg, whereas the design of the level of vacuum in the condenser PLTGU RoW can reach 703 mmHg at the load of 160 MW. The analysis shows that, keavakuman decline occurred because the RoW PLTGU condenser cooling water capacity of less as a result of the increase in head loss at the inlet tunnel and the rising sea temperature reaches 330C which fluctuates due to the influence of the season and climate. However, it is also the case of over-heat duty, which may be due to damage to the components of the turbine blade and seal so that the steam turbine output energy is still quite large, it is indicated by naikknya LMTD which reached 94% .Penurunan PLTGU Grati condenser vacuum caused losses large enough for the company, where any reduction of 10 mmHg vacuum caused an economic loss of 10 billion rupiah per year. As a follow up then, treated steps to resolve the issue of which is necessary setrategi better maintenance of the condenser and the cooling system so that the equipment can function optimally, as well as replacement in perodik on turbine components that history could potentially damage before the maintenance period Major Inspection Blade Row hereinafter that the Low Pressure Turbine Blades Stationary and Seal Strip, because the maintenance cycle is long enough (36000 hours) so that steam turbine efficiency is maintained.